Fatores dietéticos, antropométricos e socioeconômicos associados à sarcopenia em idosos: estudo transversal de base populacional - Martins, Lucélia Campos Aparecido [UNESP] (2015)
Introduction: Sarcopenia is defined as a syndrome characterized by progressive and generalized loss of skeletal muscle mass and strength that occurs with aging. It is prevalent in the elderly population and has been postulated as the main factor in the decline in strength with age, representing a health deficient state with a personal high cost. Purpose: The aim of this study was to identy the prevalence of sarcopenia and its association with dietary, anthropometric and socioeconomic factors in elderly patients in primary health care. Methodology: Cross-sectional study conducted with 136 individuals aged 60 years and older, of both sexes, assisted by the Primary Health Care of Bauru, São Paulo, from June 2013 to July 2014. Socioeconomic and demographic status, anthropometric variables and dietary profile were assessed for all individuals. The skeletal muscle mass (SMM) was obtained by Bioelectrical Impedance (BIA) and muscle strength was assessed by grip strength (FPP), measured by the analog hydraulic hand dynamometer. For the diagnosis of sarcopenia it was considered muscle wasting associated with loss of muscle strength. Logistic regression model was performed to identify the risk factors for sarcopenia considering a 5% significance level for the corresponding p-value. Results: The prevalence of sarcopenia in the study population was 37.5%, however being higher among men (66.6%). Of those individuals with sarcopenia, 50% of men and 29% of women were overweight, 35% of men and 64% of women had abnormal waist to hip ratio. Subcutaneous fat and muscle mass were lower in sarcopenic individuals. Individuals (with and without sarcopenia) had a poor quality of diet (AHEI score <P75), characterized by low consumption of vegetables, fruits, whole grains, nuts and legumes, and eggs, and high consumption of red and processed meat, sodium and trans fat. Dietary protein intake (OR: 1.174; CI: 1.043 to 1.322), zinc (OR: 6.911; CI: 1.579 to ...